2013
DOI: 10.1016/j.postcomstud.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A contested landscape: Monuments, public memory, and post-Soviet identity in Stavropol’, Russia

Abstract: Much recent literature in cultural, political and social geography has considered the relationship between identity, memory, and the urban landscape. This paper interrogates such literature through exploring the complex materialisation of memorialisation in post-Soviet Russia. Using the example of the statue of General Alexei Ermolov in Stavropol’, an analysis of the cityscape reveals interethnic tensions over differing interpretations of the life and history of the person upon whom the statue is based. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…The principal component analysis also revealed that museums and monuments tend to group together in indicating wellbeing. This is probably due to their strong ability in representing cultural identity of the people (Mazumdar & Mazumdar 2004;Foxall 2013). Considering the highest weights for principal component one and two, components one seem to identify strongly with landscape aesthetics and naturalness, and component two seem to identify strongly with social, spiritual and mental tranquillity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The principal component analysis also revealed that museums and monuments tend to group together in indicating wellbeing. This is probably due to their strong ability in representing cultural identity of the people (Mazumdar & Mazumdar 2004;Foxall 2013). Considering the highest weights for principal component one and two, components one seem to identify strongly with landscape aesthetics and naturalness, and component two seem to identify strongly with social, spiritual and mental tranquillity.…”
Section: Discussionmentioning
confidence: 98%
“…Monuments Monuments are physical symbols of real history and memory that connect the present to the past (Foxall 2013). They constitute memorials that are used to legitimize or sanctify historical personalities, groups or events in to the present social setup (Alderman & Dwyer 2009).…”
Section: 87mentioning
confidence: 99%
“…Many studies have found that due to the design disorder and a lack of collective memory during the landscape construction process, the culture of cities tended to be similar [27]. Recent work has focused on monumental landscape, from grand monuments [28], memorial rituals, places of memory [29] to museums [30]. Till studied the debate in the process of national memory reconstruction in Berlin, and believes that collective memory is built on the basis of personal and socially shared experiences [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Renowned for their skill in horseback riding and martial proficiency, the Cossacks were naturally suited to assisting in Russian military campaigns. The Cossacks were an important component of the armies of Aleksey Yermolov, a name that came to symbolize the brutality of the Russian war against the peoples of the mountains and still incites passionate contention today (Foxall 2013).…”
Section: The Attempt To Construct the "Kuban Cossack Homeland"mentioning
confidence: 99%